Морфометричний гомеостаз іхтіоценозу та екологічний статус малої річки Рівненської області - Бєдункова, Ольга; Biedunkova, Olga (Східноєвропейський національний університет імені Лесі Українки, 2015)
Рівненської області Проведено аналіз флуктуючої асиметрії представників іхтіоценозу малої річки Устя, що засвідчив: у риб зі створів із мінімальним антропогенним навантаженням стабільність розвитку була вищою, ніж в особин у межах уробекосистеми. Найвищий морфометричний гомеостаз мав карась, найнижчий – плітка та верховодка, сягаючи різниці між створами 47,9 та 60,9 %. Найтіснішими виявилися залежності від рівня забруднення поверхневих вод і дисперсією асиметрії кількості зябрових тичинок у першій зябровій дузі (R2 =0,735), а також морфометричний гомеостаз плітки (R2 =0,808) та верховодки (R2 =0,673). Fluctuating asymmetry in fish that are caught in the sections of the river with minimal anthropogenic load showed that the stability of their development has been higher than that of individuals within urobekosistem. Highest morphometric homeostasis had the roach and the perched. It turned out to be closely based on the level of contamination of surface water and the dispersion of the asymmetry in the number of gill rakers of the first gill arch (R2 =0,735), and the morphometric homeostasis roach (R2 =0,808) and the perched (R2 =0,673). Stability and development ichthyocenosis water quality rated as «average deviation from the norm», III ball. Hydrochemical indicators showed the transition from II to III class quality of surface waters. At the same time, in separate alignments results of the evaluations of the ecological status of the river on the methodology used did not match. This demonstrates the need for development of standardized criteria for assessment of hydroecosistem.
Morphometric Ichthyocenosis Homeostasis and Ecological Status of The Small River of Rivne Region
Keywords: іхтіоценоз; флуктуюча асиметрія; якість поверхневих вод; ichthyocenosis; fluctuating asymmetry; surface water quality